(untitled) (European Journal of Marketing and Economics, 2020)
The economic and social debate has been intensifying globally as a result of concerns about the increase in poverty in the world and the progressive separation between rich and poor. There is an urgent need to find ways and alternatives that can be tested and put into practice. This is an exploratory study on the perception of the Portuguese regarding Unconditional Basic Income or Universal Basic Income (UBI). UBI has defenders and opponents, both parties with convincing arguments about its practical applicability, however, conclusions cannot be reached without experience in the field and convincing results. Likewise, the idea should not be abandoned without understanding its real applicability, as its success could be important for the future development of the world. Studies on the UBI are still in their infancy. Therefore, Portugal’s contribution to the enrichment of knowledge within the topics of “the future of work” and “work of the future” and, more specifically, about UBI, is seen as urgent. In this context, we prepared and analysed a survey, having obtained 273 valid responses. The results of the qualitative analysis on which this study focuses allow us to infer that there are still many flaws in the management and leadership of human resources and, among other aspects, that, in general, the respondents would prefer to work even though they might eventually receive a UBI.